Appraisal of Soil Degradation and Health: Salinity/Sodicity and Macro-Nutrients Status in Three Tehsils of Chiniot’s Alluvial Plains - Muhammad Mazhar Iqbal; Tayyaba Naz; Muhammad Iqbal Hussain; Muhammad Akram Qazi; Abdul Ghaffar Khan; Imran Hussain; Muhammad Shakar; Sehrish Jamil; Fareeha Akram; Farah Umar; Naveed Qaisrani; Muhammad Imran Latif; et al. (Social Science Review Archives, 2025)
Salinity, sodicity, and deficiencies of macro-nutrients pose serious soil degradation threats to the sustainability of agriculture in the Indus alluvial plains of Pakistan. This study involves appraisal of soil degradation and health across Chiniot district, Punjab-provincial region represented by three tehsils: Chiniot, Bhowana and Lalain. Stratified random sampling collected 2050 composite soil samples up-to a depth of 0-15 and 15-30 cm and were analyzed for physiochemical properties following standard protocols. The results showed that among the 2050 soil sample tested, 1780 soil samples were found normal whereas 96, 86 and 88 were found saline, saline-sodic and sodic respectively. Whereas 1891 soil samples had pH ranged from 7.5 to 8.5, while 159 samples had pH > 8.5. Likewise, 106 soil samples were found light textured, 1891 had medium and 53 were found heavy textured. However, 1388 soil samples were found poor in OM, while 644 samples were medium ranged OM and 18 samples had adequate OM of the total collected soil samples. Conversely, 999 soil samples were established poor in available P, while 1049 samples were medium ranged P and 02 samples had passable soil P of the collected samples in district Chiniot. Moreover, 263 soil samples were found poor in available K, while 1683 samples were intermediate ranged K and 104 samples were tolerable soil K of the collected samples from district Chiniot. The results suggest targeted approaches to dealing with the issue of soil degradation and health such as the application of gypsum scarification, or composting and groundwater management or subsurface draining systems.